A Sharia Economic Law Perspective on Down Payment Practices in Catering Services: A Case Study - Nanda Oktaviani Astuti; Nilfatri Nilfatri; Erwina Kartika Devi; Alisyah Pitri; Reza Okva Marwendi (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The study purpose was to analyze the practice of down payments (ʿurbūn) within istisnāʿ contracts in catering service transactions at Yuriken Kitchen, a microenterprise in Pandan Lagan Village, from the perspective of Islamic economic law. The research aimed to examine whether such practices conform to sharīʿah principles and to provide recommendations for improving legal certainty and fairness in similar rural-based business contexts. Materials and methods. This study employed a qualitative, empirical-sociological approach to explore the implementation of down payment systems in a real-world setting. Data were collected through observation, interviews with the business owner and clients, and documentation. The analysis involved inductive reasoning to interpret findings within the framework of Islamic commercial jurisprudence, particularly referring to DSN-MUI fatwas and the Compilation of Islamic Economic Law (KHES). Results. Findings revealed that while down payments of 30–50% are commonly used to secure orders, transactions are conducted orally without written contracts, creating legal ambiguities and potential injustice in the event of cancellations. The current practices show partial conformity with sharīʿah—upholding trust and mutual consent—but lack formal clarity, thereby exposing parties to gharar (uncertainty) and disputes. The study also highlighted a general lack of awareness regarding the legal provisions for ʿurbūn and istisnāʿ among microentrepreneurs in the village, indicating the need for greater educational outreach on fiqh muʿāmalah. Conclusions. The research concludes that the down payment practices at Yuriken Kitchen, although rooted in local trust-based customs, are not fully aligned with the legal standards of Islamic economic law due to the absence of formal contract documentation. The study contributes a novel sociological insight by illustrating how rural social trust, while valuable, must be complemented by legally sound practices to prevent conflict and uphold justice. Promoting awareness of sharīʿah-based contract mechanisms and encouraging the use of written agreements in microenterprises is crucial for building a transparent, fair, and spiritually accountable economic environment.